Nonuniform Internal Structure of Fibrin Fibers: Protein Density and Bond Density Strongly Decrease with Increasing Diameter. (10th October 2017) - Li, Wei; Sigley, Justin; Baker, Stephen R.; Helms, Christine C.; Kinney, Mary T.; Pieters, Marlien; Brubaker, Peter H.; Cubcciotti, Roger; Guthold, Martin
Abstract : The major structural component of a blood clot is a meshwork of fibrin fibers. It has long been thought that the internal structure of fibrin fibers is homogeneous; that is, the protein density and the bond density between protofibrils are uniform and do not depend on fiber diameter. We performed experiments to investigate the internal structure of fibrin fibers. We formed fibrin fibers with fluorescently labeled fibrinogen and determined the light intensity of a fiber, I, as a function of fiber diameter, D . The intensity and, thus, the total number of fibrin molecules in a cross-section scaled as D 1.4 . This means that the protein density (fibrin per cross-sectional area), ρ p, is not homogeneous but instead strongly decreases with fiber diameter as D - 0.6 . Thinner fibers are denser than thicker fibers. We also determined Young's modulus, Y, as a function of fiber diameter. Y decreased strongly with increasing D ; Y scaled as D - 1.5 . This implies that the bond density, ρ b, also scales as D - 1.5 . Thinner fibers are stiffer than thicker fibers. Our data suggest that fibrin fibers have a dense, well-connected core and a sparse, loosely connected periphery. In contrast, electrospun fibrinogen fibers, used as a control, have a homogeneous cross-section.